Is the second screen becoming the first? An exploratory study of emerging multi-screening practices - Dias, Patrícia (2022)
The proliferation of mobile devices with internet access, along with increasing rates of adoption of smartphones and tablets, are resulting in the emergence of new use practices, among which simultaneous activities in different screened-devices. This paper discusses the concept of 'second screening', usually referring to using the mobile phone while watching television and suggesting that the TV is the main focus of attention, advocating 'multi-screening' instead, as there are several different binomials of simultaneous activities in screened-media, most of which involve the smartphone as the preponderant medium, and that may be simultaneous, sequential or alternate. Triangulating results from an online survey to multi-screeners and from interviews to relevant industry stakeholders, our research identifies emerging multi-screening practices, the motivations behind them, and the preponderance of smartphones as the most engaging medium. This paper results from the first stage of an ongoing project on multi-screening that aims to explore new business models and offers related both to platforms and to content, trying to match the industry's offers to the users' needs, preferences and expectations.